F88. CHILDHOOD SEXUAL ABUSE AND ADULT SEXUAL BEHAVIOR IN WOMEN WITH ANTIPSYCHOTIC-INDUCED HYPERPROLACTINEMIA. (9th April 2019) - Feldman, Stephanie; Powell, Megan; Wehring, Heidi; Sayer, Mackenzie; Hackman, Ann; Buchanan, Robert; Adams, Heather; Richardson, Charles; Vyas, Gopal; McMahon, Robert; Earl, Amber; Sullivan, Kelli; et al.
Abstract: Background: Hyperprolactinemia is a common adverse event associated with antipsychotic treatment, particularly in those treated with risperidone, paliperidone and haloperidol. Adverse consequences are related to elevated prolactin but less is known about contributors to variability seen in women with some people experiencing high levels Prolactin secretion occurs from the pituitary gland through dopamine blockade in the tuberoinfundibular dopamine pathway. Data suggests that Adverse Childhood Experiences (ACE) lead to long lasting effects on both physical and mental health, including pituitary and adrenal gland abnormalities. We report sexual behavior and abuse history and examined the relationship of childhood sexual abuse to adult sexual dysfunction and prolactin levels in this population. Methods: We have included data from a one-time screening visit to examine childhood sexual abuse using the Childhood Experience of Care and Abuse questionnaire (CECA.Q) as collecting sexual behavior and sexual dysfunction using the Arizona Sexual Experiences Scale (ASEX). Sexual dysfunction was characterized as a score ≥16. All women were recruited with high prolactin levels (>24 ng/ml) and with a psychotic disorder diagnosis (N=43) and between the ages of 18–50 years. Results: The mean prolactin in this sample was 88.5 ± 56.02 ng/ml. The age at first sexual encounter was young, with 38% (15/40) women having sexual relations at age 13 or younger and 5 (12%) have engaged in sexual behavior under the age of 10 years. We found that 37% (16/43) of the women had 10 or more lifetime partners. However, most women have never been pregnant (26/43 60%). Seventeen women have experienced pregnancy (40%) with 51 total pregnancies. This resulted in 31 children. Most women select men as their sexual partner preference (84%) and 3 women identified as LGBTQ (7%). Most women currently have no active sexual partner (29/43 67%), 3 have one partner (7%) and 11/43 (26%) have two current partners. Unwanted childhood sexual experiences occurred in 15/43 women (35%) before the age of 17 with a mean age of 8.2 ± 3.5 years when unwanted experiences began and 10/15 (67%) from a relative. Mean sexual function was 20.4 ±7.2 on the ASEX scale (70% having sexual dysfunction). Prolactin levels were 21% higher in those with sexual abuse histories but not significantly different (F=1.95. df=15, p=0.15). Discussion: ACEs are high in women with psychotic disorders with over 1/3 having sexual abuse in childhood. In this group of women, they were exposed to sexual behavior at a young age. Prolactin levels tended to be higher in women with unwanted sexual experiences in childhood and sexual dysfunction occurs in the majority of women. Hormonal and sexual issues as well as prolactin elevations seen in adults may be associated with ACE in women who develop schizophrenia.